Critical Success Factors for Limited Service Hotels in Malaysia - Wong, Chee Keng (2015)
Critical success factors were used originally in Information technology areas when it was first introduced but has since been applied generically in other industries. This study explores the critical success factors for limited service hotels in Malaysia from both customer and hotel operator/ business owners’ perspective. The literature presents information from tourism in general and in Malaysia, definition of limited service hotels and its relevance to the hospitality industry in Malaysia, critical success factors and its application in various industries. Both qualitative and quantitative research methods were used to collect primary data. 61 online survey respondents and 5 hotel operators/ business owners (through individual interviews) participated in the study. The importance performance analysis (IPA) method was used to evaluate the findings from the survey and interview results. The critical success factors used in this research are divided into 9 main categories; Core Product: Hotel, Core Product: Room, Service Quality, Human Resources, Location, Strategic Control, Pricing, Promotion and Use of Internet. Research results reveal that overall customers and hotel operators were in agreement that the identified CSFs were all deemed relevant and important with emphasis given to factors related to Core Product: Hotel and Room, Service Quality, Location, Pricing and the Use of Internet. Recommendations were provided to help hotel operators in identifying the right customers, managing social media, implementation of gamification CRM solutions, implementation of revenue/ yield management solutions and the importance of providing free internet.